Dietary behaviour changes to improve nutritional quality and health outcomes - Linda C. Tapsell (KeAi Communications Co., Ltd., 2017)
This narrative review examines the changes required in dietary behaviours to address the current global burden of disease resulting from diet-associated cardiometabolic dysfunction. Beginning with known relationships between nutritional factors and health outcomes, the review identifies a number of problems with current dietary behaviours, using examples from the Australian context. Implications for practice are then discussed drawing on insights from research in dietary trials. From a concerted research effort across the globe, the effects of foods, food components and dietary patterns on cardiometabolic parameters have been reasonably well exposed. The evidence base for these effects underpins dietary guidelines, which aim to meet nutritional requirements and protect against cardiometabolic disease. Thus foods recommended in dietary guidelines tend to be consistent with research that identifies foods that appear protective and those that appear detrimental to health. The need for dietary behaviour change is apparent through analyses that have exposed increasing consumption of detrimental foods, despite the availability of healthy foods. However, behaviour change is a complex area, and where weight loss is also required, there is high level evidence that interdisciplinary efforts combining diet, physical activity and psychological support are warranted. Insights from dietary trials and research indicate that focussing on foods and dietary patterns is integral to the specific dietary change required for health outcomes, but social and behavioural factors will influence the achievement of these changes. Keywords: Diet, Nutritional quality, Lifestyle-related disease